Sistem Penunjang Keputusan Pencarian Rute Terpendek Menggunakan Metode Dijkstra Menuju PAUD dan TK - Putra, M.; Candra, Rina (STIKOM Tunas Bangsa Pematangsiantar, 2024)
In life, the search for the shortest route in finding a place always goes to the destination location is a study which has been studied a lot lately and has become a problem. This will be very useful to be implemented in several cases that require a high level of time efficiency such as route search, location search, and so on. Determining the shortest path can be obtained using Dijkstra's Algorithm. The use of Dijkstra's algorithm is widely used to find the shortest route because this algorithm calculates the path based on the shortest distance traveled in each path. This algorithm was chosen because it was developed as an efficient algorithm for finding the shortest path based on a positive weight, from a starting point to all other points using software used to help describe the system, namely DFD.